Demographic characteristics, leadership styles, job attitudes and personality as predictors of job performance among civil servants in Southwest Nigeria (2014)
This purpose of this study was to investigate the predictive influence of demographic characteristics, leadership styles, job attitudes and personality on jot performance among civil servants in Southwest Nigeria. The sample consists of 400 civil servants (males = 275 females = 125) randomly selected from Southwestern Nigeria. Measures of demographic form leadership styles, job attitudes, personality and job performance were administered to the civil servants Data collected mere analysed using multiple regression analysis. Results of the study showed that job performance had a significant predictive relationship with leadership styles, demographic characteristics job attitudes and personality - a strong relationship of job performance and neuroticism, openness to experience and agreeableness among the civil servants. Based on the findings, it was recommended that government and private organisations should ensure that employees have the opportunity for training and development so as to enhance job performance in organisations.